Hot compression deformation characteristics of Mg-Mn alloys - 方超 张静 廖爱林 薛绍展 袁付庆 潘复生 (Transactions of Nonferrous Metals Society of China, 2010)
The hot deformation behaviors of solution treated Mg-1.8Mn-0.4Er-0.2Al alloys were investigated by means of compression tests on Gleeble-1500 in strain rate range of 0.01-10s^-1,deformation temperature range of 250-450℃ and a true strain of 0.6.The constitutive relationships among flow stress,strain rate and deformation temperature were described by Arrhenius-type equations,based on the fact that the material constants could be calculated under a wide range of strains.The results show that the flow stress of the experimental alloy decreases with temperature increasing and strain rate decreasing.Under the experimental conditions,the products of constant α and n in the constitutive equation are stable within certain strains,and the deformation activation energy ranges from 160 to 220 kJ/mol.It is proved that the values of calculated flow stress are close to the experimental results with average error of 2.01%.